Estudo e análise comparativa de topologias de filtros ativos de potência paralelos implementados em sistemas elétricos trifásicos a quatro fios - Bacon, Vinícius Dário (2015)
This work deals with the study and comparative analyses of four Shunt Active Power Filters (SAPFs), which are implemented employing the Split-Capacitor (SC), Four-Leg (4L), Three Full-Brige (3FB) and Neutral-Point-Clamped (NPC) inverter topologies. The SAPFs carry out reactive power compensation, as well as harmonic suppression in three-phase four-wire electrical systems. In order to perform the aforementioned conditioning, algorithms based on the synchronous reference frame are used to compute the compensation references currents. The current plant mathematical models, which are related to the compensation currents, are obtained in the abc reference frame considering the studied SAPFs. Only the 4L topology has the current plant model is obtained in the stationary reference frame αβ0. Thereby, the current control is implemented in αβ0-axes for only the 4L SAPF, while for the other three SAPFs the control is implemented in the abc-axes. The model that represents the voltage plant, which is related to DC-bus voltage, is also presented involving all the studied SAPF topologies. The mathematical modelling are unified, meaning that all the SAPF models can be found from one of them. Thus, from the unified model, it is possible to carry out a unified controller gains design, In other words, the controller gains obtained to a specific SAPF topology can be used to find the controller gains for the other ones. This project methodology allows the obtaining of the same control performance for all the SAPF topologies. In order to validate the theoretical analyses, as well as to evaluate the SAPFs performances, computational simulations and experimental tests are carried out. In addition, comparative analyses of the studied SAPFs are presented, considering the topological features, costs and performance. These comparative analyses allow the determining of the suitable applications for each one of the SAPF topologies.